Analysis of Bank Health Assessment Using the RGEC Method (Risk Profile, Good Corporate Governance, Earning, Capital) in Private Banks Listed on the Indonesia Stock Exchange in 2020-2023 - Nining, Nining Yulianti; Purwanto, Kelik; Ermawati , Eka (Universitas Islam Lamongan, 2024)
The banking sector is always required to improve its performance. Given the importance of knowing the financial performance, Indonesian banking has made many regulations related to measuring bank health in accordance with Law No. 13 of 2011 concerning bank health. This study aims to determine and analyze bank health through the RGEC method (Risk Profile, Good Corporate Governance, Earning and Capital) in Private Banks Listed on the Indonesia Stock Exchange in 2020-2023. The data source used is secondary data in the form of financial reports for the period 2020-2023. The type of research in this journal is Qualitative research. The results of this study indicate that the condition of the bank is very healthy because it has a very good management capacity in selecting customers who will receive credit loans, is very effective in utilizing its activities to obtain company profits and has very good capital adequacy. Meanwhile, the results of the study using Good Corporate Governance indicate that the condition of the bank is not running well so that it cannot be said to be a trusted bank